2021
DOI: 10.1093/neuonc/noab023
|View full text |Cite
|
Sign up to set email alerts
|

A serum-based DNA methylation assay provides accurate detection of glioma

Abstract: Background The detection of somatic mutations in cell-free DNA (cfDNA) from liquid biopsy has emerged as a non-invasive tool to monitor the follow-up of cancer patients. However, the significance of cfDNA clinical utility remains uncertain in patients with brain tumors, primarily because of the limited sensitivity cfDNA has to detect real tumor-specific somatic mutations. This unresolved challenge has prevented accurate follow-up of glioma patients with non-invasive approaches. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 46 publications
4
52
0
Order By: Relevance
“…These results from urine samples from glioma echoed our previous work, which identified 63% of plasma samples from glioma patients with 94% specificity using another RF model based on integration of fragmentation features in plasma cfDNA (Mouliere et al , 2018a ). Together with other studies that utilize methylation patterns in plasma (Nassiri et al , 2020 ; Sabedot et al , 2021 ), our work suggests that despite a low detection rate of mutations, epigenetic signals (i.e., fragmentation patterns) can be robustly detected in the plasma and also urine of glioma patients.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These results from urine samples from glioma echoed our previous work, which identified 63% of plasma samples from glioma patients with 94% specificity using another RF model based on integration of fragmentation features in plasma cfDNA (Mouliere et al , 2018a ). Together with other studies that utilize methylation patterns in plasma (Nassiri et al , 2020 ; Sabedot et al , 2021 ), our work suggests that despite a low detection rate of mutations, epigenetic signals (i.e., fragmentation patterns) can be robustly detected in the plasma and also urine of glioma patients.…”
Section: Discussionsupporting
confidence: 80%
“…While methylation‐based detection, cell‐free DNA genome‐wide fragmentation, tumor‐derived mitochondrial DNA, exosomes, vesicles, and tumor‐educated platelets have all been proposed as alternative methods for plasma‐based detection of glioma‐derived mutant DNA, these alternative strategies provide limited information about the tumor genome (Best et al , 2015 ; Moss et al , 2018 ; Mouliere et al , 2018a ; Shen et al , 2018 ; Mair et al , 2019 ; Nørøxe et al , 2019 ; van der Pol & Mouliere, 2019 ; Sabedot et al , 2021 ). Through tumor‐guided sequencing, we have identified mutations in the plasma and urine of GBM patients and thus demonstrate the potential to track tumor‐specific mutations with a high specificity that may be important for monitoring tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, whole genome strategies have dramatically expanded the identification of aberrantly methylated genes [15,47], allowing systematic approaches that seek for maximum accuracy by the generation of diagnostic signatures. Thus, in addition to classical biomarkers of diagnosis based on single methylated genes [43,48], some specific DNA-methylation-based signatures have been described for the detection of several tumours, such as prostate cancer [49,50], hepatocellular carcinoma [51], and glioma [52]. However, virtually no diagnostic biomarker or signature based on DNA methylation has been proposed for TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Although the low ctDNA content limits the utility of WGBS or RBBS for non-invasive CNS tumor diagnosis, one recent study by Sabedot et al used 2–100 ng of serum ctDNA for WGBS and showed efficacy in discriminating and monitoring gliomas [ 71 ]. Using 38 glioma samples and 42 non-glioma control samples the authors developed a glioma epigenetic liquid biopsy score called GeLB that was highly accurate is detecting gliomas versus non-glioma patient with a sensitivity of 100% and specificity of 97.8%.…”
Section: Circulating Tumor Dnamentioning
confidence: 99%